TRENDS IN ISLAMIC EDUCATION RESEARCH: A BIBLIOMETRIC PERSPECTIVE ON THE GLOBAL LITERATURE 2014 -2024 - Nurhikmah, Cece (Bajang Institute, 2025)
Study This aiming For identify global trends in study Islamic education during period 2014–2024, with focus on pattern publication, theme main, and collaboration writer. Using approach quantitative based on analysis bibliometrics, data obtained from the Scopus database via keyword search​ such as